How I treat medulloblastoma in children - Amita Mahajan (Indian Journal of Medical and Paediatric Oncology)
Medulloblastoma (MB) is the most common malignant tumor of the central nervous system in children with up to a third of these tumors presenting in children under 3 years of age. Its exquisite radio and chemosensitivity renders high cure rates in children in whom optimal resection has been achieved. Optimal surgery followed by radiation alone can cure about half of these children. The addition of chemotherapy has improved the outcomes dramatically and over 70% of children over 3 years of age with optimal resection and no metastasis can expect to be cured. Increasingly, the focus is on limiting the long-term sequelae of treatment. Precise molecular characterization can enable us to identify patients who can achieve optimal outcomes even in the absence of radiation. Insights into disease biology and molecular characterization have led to dramatic changes in our understanding, risk stratification, prognostication, and treatment approach in these children. In India, there is limited access to molecular profiling, making it challenging to apply biology driven approach to treatment in each child with MB. The Indian Society of Neuro-Oncology guidelines and the SIOP PODC adapted treatment recommendations for standard-risk MB based on the current evidence and logistic realities of low-middle income countries are a useful adjunct to guide clinical practice on a day-to-day basis in our setting.